การเสริมสร้างพลังอำนาจกับความยึดมั่นผูกพันต่อองค์การของพยาบาล วิชาชีพ โรงพยาบาลธรรมศาสตร์เฉลิมพระเกียรติ; Empowerment and Organization Commitment of Professional Nurses in Thammasat University Hospital - สาสังข์ เนตรนภา; เพ็ญศิรินภา นิตยา; ประเสริฐชัย อารยา (Journal of The Royal Thai Army Nurses, 2016)
การวิจัยเชิงสำรวจนี้มีวัตถุประสงค์เพื่อศึกษา (1) ปัจจัยส่วนบุคคล การเสริมสร้างพลังอำนาจและความยึดมั่นผูกพันต่อองค์การของพยาบาลวิชาชีพ (2) ความสัมพันธ์ระหว่างปัจจัยส่วนบุคคล และการเสริมสร้างพลังอำนาจกับความยึดมั่นผูกพันต่อองค์การของพยาบาลวิชาชีพ และ (3) ปัญหาอุปสรรคและข้อเสนอแนะเกี่ยวกับการเสริมสร้างพลังอำนาจ และความยึดมั่นผูกพันต่อองค์การของพยาบาลวิชาชีพ โรงพยาบาลธรรมศาสตร์เฉลิมพระเกียรติ ผลการศึกษาพบว่า (1) พยาบาลวิชาชีพโรงพยาบาลธรรมศาสตร์เฉลิมพระเกียรติ มีอายุระหว่าง 20 - 48 ปี อายุเฉลี่ยเท่ากับ 30 ปี มีประสบการณ์การทำงานที่โรงพยาบาลธรรมศาสตร์เฉลิมพระเกียรติ เฉลี่ย 6.70 ปี ส่วนใหญ่มีสถานภาพโสดเป็นพนักงานมหาวิทยาลัยและลูกจ้างประจำ ลักษณะการอยู่เวรเป็นเวรเช้า - บ่าย - ดึก มีภูมิลำเนาต่างจังหวัดในภาคอื่น ๆ ที่ไม่ใช่ภาคกลาง คิดเป็นร้อยละ 45.50 รองลงมากรุงเทพฯ และปริมณฑล คิดเป็นร้อยละ 31.40 ระดับความคิดเห็นของพยาบาลวิชาชีพต่อการได้รับการเสริมสร้างพลังอำนาจอยู่ในระดับมาก ความยึดมั่นผูกพันต่อองค์การอยู่ในระดับปานกลาง (2) ปัจจัยส่วนบุคคลไม่มีความสัมพันธ์กับความยึดมั่นผูกพันต่อองค์การ ส่วนการเสริมสร้างพลังอำนาจทั้งโดยรวมและรายด้านมีความสัมพันธ์ทางบวกกับความยึดมั่นผูกพันต่อองค์การ อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.001 และ (3) ปัญหาอุปสรรคที่สำคัญในมุมมองของพยาบาลวิชาชีพ คือ การสื่อสารในองค์กรล่าช้า โอกาสก้าวหน้าน้อย ไม่มีแนวทางการพัฒนาบุคลากรที่ชัดเจน โดยเสนอแนะให้มีช่องทางการสื่อสารที่สะดวกรวดเร็ว เข้าถึงข้อมูลได้ง่าย จัดทำแนวทางการพัฒนาบุคลากรที่ชัดเจน รวมทั้งจัดสรรเวลาทำงานให้ยืดหยุ่นเอื้อต่อการพัฒนาบุคลากรได้ The objectives of this survey research were to study : (1) personal factors, empowerment and organizational commitment, (2) the relationships between personal factors, empowerment, and organizational commitment, and (3) problems and suggestions related to empowerment and organizational commitment, all of professional or registered nurses in Thammasat University Hospital. The study was conduced among 134 out of 563 full-time registered nurses having worked at the hospital for at least one year, selected using the stratified random sampling method according to nursing departments. The research tool was a questionnaire with the reliability values of 0.82 for empowerment and 0.78 organizational commitment. Statistics used in data analysis were percentage, mean, standard deviation, Pearson product-moment correlation coefficients and chi - square test. The findings revealed that : (1) The registered nurses at the hospital were 20 - 48 years old (mean, 30 years), had an average work experience at the hospital of 6.7 years, were mostly single, worked as university staff and permanent employees, and had 8 - hour shifts; 45.5% of them were originally from non-central regions and 31.45% from Bangkok and its vicinity. Their empowerment was at a high level, while organizational commitment was at a moderate level. (2) Their personal factors were not associated with the organizational commitment, but the empowerment was significantly and positively related to organizational commitment (p - value 0.001). (3) Their major problems and obstacles were communication delays, little career advancement opportunities, and lack of concrete personnel development guidelines. It is suggested that there should be rapid communication channels, easy access to information, personnel development guidelines, and flexible working time arrangements to allow for professional development.